The Influence of Transparency, Accountability, and Managerial Competence on Village Fund Management (A Study in Villages Located in Pulubala District, Gorontalo Regency, Gorontalo Province) - Nursila Moha; Ayu Rakhma Wuryandini; Nurharyati Panigoro (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to determine the influence of transparency, accountability, and managerial competence on the management of village funds in villages in Pulubala District, Gorontalo Regency. The method used in this study is a quantitative method using primary data obtained through the distribution of questionnaires to respondents. The sampling technique used is purposive sampling with the criteria of village officials directly involved in the management of village funds. The data analysis technique used in this study is multiple linear regression analysis with the assistance of the IBM SPSS Statistics 2026 program. Research results show that transparency does not have a significant effect on village fund management. Accountability also does not have a significant effect on village fund management. Meanwhile, managerial competence has a positive and significant effect on village fund management. Simultaneously, transparency, accountability, and managerial competence have a significant effect on village fund management.